Silent Love The Annotation and Interpretation of Nabokov's "The Real Life of Sebastian Knight" - de Vries, Gerard (Academic Studies Press, 2016)
The Real Life of Sebastian Knight is one of Vladimir Nabokov's most autobiographical novels and it has often been observed that Sebastian's passionate affair with the femme fatale Nina Rechnoy is a dramatized extension of Nabokov's infatuation with Irina Guadanini. In this book it is shown that the novel also conceals another, secluded, love affair Sebastian had with a man, which reflects the main episode in the life of Nabokov's brother Sergey. By pursuing many biographical and literary references and allusions, and by disregarding the deceptive guiding by the narrator (Sebastian's half-brother), this moving story about Sebastian's silent love becomes brightly visible.